Functional Magnetic Resonance Spectroscopy: The “New” MRS for Cognitive Neuroscience and Psychiatry Research - Stanley, Jeffrey A.; Raz, Naftali (Frontiers in Psychiatry, 2018)
Proton magnetic resonance spectroscopy (¹H MRS) is a well-established technique for quantifying the brain regional biochemistry in vivo. In most studies, however, the ¹H MRS is acquired during rest with little to no constraint on behavior. Measured metabolite levels, therefore, reflect steady state concentrations whose associations with behavior and cognition are unclear. With the recent advances in MR technology - higher-field MR systems, robust acquisition techniques and sophisticated quantification methods - ¹H MRS is now experiencing a resurgence. It is sensitive to task-related and pathology-relevant regional dynamic changes in neurotransmitters, including the most ubiquitous among them, glutamate. Moreover, high temporal resolution approaches allow tracking glutamate modulations at a time scale of under a minute during perceptual, motor, and cognitive tasks. The observed task-related changes in brain glutamate are consistent with new metabolic steady states reflecting the neural output driven by shifts in the local excitatory and inhibitory balance on local circuits. Unlike BOLD-base fMRI, this form of in vivo MRS, also known as functional MRS (¹H fMRS), yields a more direct measure of behaviorally relevant neural activity and is considerably less sensitive to vascular changes. ¹H fMRS enables noninvasive investigations of task-related glutamate changes that are relevant to normal and impaired cognitive performance, and psychiatric disorders. By targeting brain glutamate, this approach taps into putative neural correlates of synaptic plasticity. This review provides a concise survey of recent technological advancements that lay the foundation for the successful use of ¹H fMRS in cognitive neuroscience and neuropsychiatry, including a review of seminal ¹H fMRS studies, and the discussion of biological significance of task-related changes in glutamate modulation. We conclude with a discussion of the promises, limitations, and outstanding challenges of this new tool in the armamentarium of cognitive neuroscience and psychiatry research.